2019
DOI: 10.1017/s1754470x19000230
|View full text |Cite
|
Sign up to set email alerts
|

A review of the relationship between intolerance of uncertainty and threat appraisal in anxiety

Abstract: The development and conceptual relationship of the constructs of threat appraisal (TA) and intolerance of uncertainty (IU) are explored in the context of anxiety disorders. A narrative review tracking the development of these constructs and their relationship is undertaken. There is some evidence to suggest that the interaction between the components of threat appraisal (probability × cost) may partially account for or provide a theoretical framework which explains presenting levels of anxiety. Furthermore, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Beck et al, 1985), Salkovskis (1991Salkovskis ( , 1996 proposed an integrated account across disorders that anxiety can be understood as a response to the perceived likelihood of actual danger multiplied by the perceived awfulness or cost of that danger mitigated by the sum of coping and rescue factors. Milne et al (2019) provide a review of the development of these ideas and summarise the limited research that has directly tested this model. They conclude that while the full equation has rarely been tested with the denominator terms included (rescue and coping), there is good evidence for the two separate components of likelihood and cost and limited evidence that the multiplicative component of the model predicts anxiety over and beyond the additive effects of likelihood and cost.…”
Section: Threat Models Of Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…Beck et al, 1985), Salkovskis (1991Salkovskis ( , 1996 proposed an integrated account across disorders that anxiety can be understood as a response to the perceived likelihood of actual danger multiplied by the perceived awfulness or cost of that danger mitigated by the sum of coping and rescue factors. Milne et al (2019) provide a review of the development of these ideas and summarise the limited research that has directly tested this model. They conclude that while the full equation has rarely been tested with the denominator terms included (rescue and coping), there is good evidence for the two separate components of likelihood and cost and limited evidence that the multiplicative component of the model predicts anxiety over and beyond the additive effects of likelihood and cost.…”
Section: Threat Models Of Anxietymentioning
confidence: 99%
“…In a further study by Milne et al . (2017), 295 community adults (75% were 25 years or older), participated in a vignette-based study. Thirty per cent met criteria for elevated anxiety.…”
Section: Are Threat and Iu Separable In Anxiety?mentioning
confidence: 99%
“…Conversely, the MFWU group seeks to target the uncertainty component (B), to increase knowledge and awareness of the responses to uncertainty discomfort and to support individuals to build a new relationship with uncertainty, where safe uncertainty can be more accurately assessed and uncertainty discomfort can be tolerated, with a likely corresponding effect on symptoms. Previous research suggests that a reduction in IU can have a corresponding effect on symptoms of common difficulties (Milne et al, 2019;p. 12).…”
Section: Approachmentioning
confidence: 97%
“…The 'Making Friends with Uncertainty' group was novel because it focused on a single transdiagnostic process for people with different and co-morbid anxiety disorders. Studies have shown that IU appears in 'varying degrees from non-clinical to clinical populations : : : and is applicable to people in everyday life situations' (Milne et al, 2019;p. 8).…”
Section: Placing Findings In the Context Of Literaturementioning
confidence: 99%
“…To be more specific, individuals with IU perceive uncertainty as stressful, annoying and worrying, and they believe that uncertain situations must be avoided. It has been reported that IU is one of the cognitive processes that lead to the development of many psychiatric disorders, primarily anxiety, and that it is one the parameters that should be considered in assessing such disorders (Milne et al, 2019; Tanovic et al, 2018). Although the uncertainty-anxiety and IU-anxiety relationship has been well established, only a few studies have investigated the effect of uncertainty and IU on anxiety (Chen et al, 2018; Oglesby & Schmidt, 2017; Rosen & Knäuper, 2009).…”
Section: Introductionmentioning
confidence: 99%